Ecological data of Lepidosaphes gloverii (Hemiptera: Diaspididae) in Greece - Stathas, G.J. (ENTOMOLOGIA HELLENICA, 2004)
In June 2001 the scale Lepidosaphes gloverii (Packard) (Hemiptera: Diaspididae) was found on orange trees in Peloponnesus, Gastouni area, (Southwestern Greece). From the day it was first recorded until August 2003 observations on orange trees were held both in field and laboratory, concerning the biology and ecology of this scale. L. gloνerii infests mainly the upper surface of the leaves and the fruits and less the shoots of the tree. During the period April to August 2002 the scale completed 3 overlapping generations. Female fecundity ranged between 32 and 57 eggs. Chilocorus bipustulatus (L.) (Coleoptera: Coccinellidae) and Rhyzobius lophanthae Blaisdell (Coleoptera: Coccinellidae) predators were found to feed upon this scale. In Ju1y 2002 a mass release of those predators took place on infested orange trees. To assess the action of these predators, observations were conducted in both field (by shaking the branches of the trees and counting the number of the predators) and laboratory (by counting the predated scales found on leaves). The release of predators contributed to the decrease of infestation density of trees. C. bipustulatus developed significantly higher populations than R. lophanthae.